Mengenal Konsep Pembelajaran Abad 21 dan Peran Guru dalam Pembelajaran Abad 21 - Ema Deva Amilia; Cendy Lestari; Masayu Laila Nadalina; M Juniansyah; Sani Safitri; Rani Oktapiani (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
The advancement of knowledge and technology in the 21st century has changed human life patterns and demands a transformation in the world of education to be able to prepare students to face global challenges. 21st-century education emphasizes the mastery of critical, creative, communicative, collaborative skills, and technological literacy needed in the digital era.The purpose of this study is to investigate the idea of 21st-century learning, relevant learning models, and the role of teachers as facilitators, innovators, and agents of change in the modern learning process. This study uses a library research strategy by reviewing numerous scientific materials linked to 21st-century competencies, Learning methods including cooperative Learning, Project Based Learning, Problem Based Learning, and Discovery Learning, as well as the TPACK framework as a basis for technology integration. The study’s findings show that 21st-century learning requires the implementation of a learner-centered approach and the planned use of technology to raise the standard of learning procedures and results. In addition, teachers have a strategic role in guiding to enable pupils to acquire higher order thinking abilities and adapt to changing times. The implications of this study emphasize the importance of strengthening teacher competencies and implementing innovative learning models is an attempt to raise educational standards in the global era.